Manufacturing and characterization of waste polyethylene terephthalate-based functional composites reinforced with organic and inorganic fillers - Deniz, Sermin; Aydogmus, Ercan; Kar, Filiz; Arslanoglu, Hasan (Taylor & Francis Inc, 2024)
Many fillers are employed as reinforcement in polymeric materials to improve their properties and reduce expenses. This research aims to improve the mechanical and thermophysical properties of waste polyethylene terephthalate (WPET). Using recycled materials is also one of the study's objectives in support of environmental preservation. Glass fiber (3 wt.%, 6 wt.%, 9 wt.%, and 15 wt.%), calcium carbonate (5 wt.%, 15 wt.%, and 25 wt.%), and corn starch (3 wt.%) have all been added to WPET in different ratios to create composite materials. The mechanical strength, Shore D hardness tests, scanning electron microscopy (SEM), thermogravimetric analysis (TGA), Fourier transform infrared (FTIR) spectroscopy, and thermal, mechanical, physical, and chemical properties of these composites have all been investigated. It has been shown that while the amount of starch in the samples remains constant, the hardness increases as the amount of calcite and glass wool increases. The thermal conductivity does not significantly change as the ratio of glass fiber increases, notwithstanding a modest drop Nonetheless, the thermal conductivity values rise in tandem with the calcium carbonate (CaCO3) ratio. [GRAPHICAL ABSTRACT]
Keywords: Calcium carbonate; characterization; corn starch; Functional composite; glass fiber; waste polyethylene terephthalate